USEFULNESS OF MODAL ANALYSIS FOR EVALUATION OF MILLING PROCESS STABILITY - PIEŚKO, Paweł; ZAWADA-MICHAŁOWSKA, Magdalena (Applied Computer Science, 2017)
The paper presents evaluation of modal analysis usefulness for determination of milling process stability. In the first phase of the study experimental modal analysis was performed and using CutPro 9.5 software, stability lobes were generated. In the next step, machining tests were carried out. The last stage of the experiment involved verification of modal analysis usefulness for evaluation of milling process stability based on surface roughness measurements. Conducted research allowed to state that modal analysis can be a useful tool for determining milling process stability.